Diffusing Anand: Implications of Establishing a Dairy Co-operative in a Village in CentralKerala - Shanti George (Economic and Political Weekly, Vol. 19, No. 51/52 (Dec. 22-29, 1984), pp. 2161-2170, 1984)
This paper describes the findings of a livestock survey carried out in a small village in central Kerala during April 1984. The data is presented as interesting in itself since the village studied is multi-religious, multi-caste, multi-caste and multi-occuDational, situated on the periphery of an area of rapid industrial development. The data is also used to weigh one aspect of present dairy policy, viz, the establishment of Anand pattern' milk pro- curement co-operatives in villages, by speculating as to the effect such a co-operative would have on patterns of livestock holding and milk consumption if established in the village under study